Imperfuração congênita do óstio uretral externo associada à persistência de úraco em bezerra Nelore: Relato de caso - Alonso, J. M. [UNESP]; Rodrigues, C. A. [UNESP]; Alves, A. L.G. [UNESP]; Watanabe, M. J. [UNESP]; Hussni, C. A. [UNESP] (FapUNIFESP (SciELO), 2017)
Urethral imperforation associated or not with urachal patency is rare, when concomitant, the animal maintains urinary flow through umbilical via, but when the treatment is performed storage of urine occurs and can culminate in complications like bexigoma, hydrourether, and vesical rupture. A nelore calf with 20 days of age, was attended with urachal patency, conservative treatment with searing substance (10[%] iodine) was prescribed. Return for surgical treatment was recommended if no resolution was achieved. After 30 days, the animal returned with abdominal distension and history of gradual decrease in urinary flow without urination via urethra. Urethral catheterization was attempted, unsuccessfully, and sonographic evaluation revealed vesical distention with approximately seven liters of content, hydrourether and hydronephrosis. cystocentesis and vesical deflation was performed. Surgical approach of the bladder was performed and a new ostium for the urethra in the vaginal vestibule was created by retrograde via. Urachal was removed and urethral catheterization was maintained for 10 days. Following 30 days of pos operative procedure, the animal was discharged.
Congenital external urethral ostium imperforation associated to urachal persistence in Nelore calf: Case report